Walking towards the splendour of God -- a directory of shrines - De los Reyes, Felelizabeth M.; Association of Shrine Rectors and Promoters of Pilgrimages in the Philippines (Muntinlupa City Association of Shrine Rectors and Promoters of Pilgrimages in the Philippines, 1995)
It discusses various religious shrines in the Philippines.
On cover: A Directory of religious shrines in the Philippines.
Keywords: Christian shrines -- Philippines -- Directories; Shrines -- Philippines -- Directories